Politics and Society in Contemporary Spain From Zapatero to Rajoy - Field, B.; Field, B.; Botti, A.; Botti, A. (Europe in Transition: The NYU European Studies Series, 2013)
This edited volume examines the political, social, and economic developments in contemporary Spain, with a particular focus on the period of the Socialist government (2008-11), the 2011 elections, and the challenges facing Spain and the new Popular Party government.